2009
DOI: 10.1097/prs.0b013e3181a80557
|View full text |Cite
|
Sign up to set email alerts
|

Soft-Tissue Reconstruction of External Hemipelvectomy Defects

Abstract: Hemipelvectomy is associated with high wound morbidity. When the hemipelvectomy flap has a musculocutaneous design, hernias are exceedingly rare. Although immediate reconstruction is accomplished with a hemipelvectomy flap in the vast majority of cases, secondary reconstructions are often required for management of wound complications. For large defects, a contralateral inferiorly based rectus abdominis muscle or musculocutaneous flap is the reconstruction of choice. The rectus abdominis muscle should therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 26 publications
1
49
0
1
Order By: Relevance
“…10 Several other authors have also recently reported similarly high rates of wound complications following surgery for pelvic tumours. 2,5,9,11 In a study of 160 patients who underwent primary closure of the wound following hemipelvectomy, Senchenkov et al 12 found that wound complications were the most common causes of post-operative morbidity, including infection in 62 patients (39%) and partial flap necrosis in 41 (26%). In a series of 110 patients after resection for pelvic sarcomas, Hillmann et al 2 found that 44 (40%) had wound complications such as infection, skin problems or haematoma formation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…10 Several other authors have also recently reported similarly high rates of wound complications following surgery for pelvic tumours. 2,5,9,11 In a study of 160 patients who underwent primary closure of the wound following hemipelvectomy, Senchenkov et al 12 found that wound complications were the most common causes of post-operative morbidity, including infection in 62 patients (39%) and partial flap necrosis in 41 (26%). In a series of 110 patients after resection for pelvic sarcomas, Hillmann et al 2 found that 44 (40%) had wound complications such as infection, skin problems or haematoma formation.…”
Section: Discussionmentioning
confidence: 98%
“…[3][4][5][6][7][8] An overall rate of wound complications of up to 30% to 40% has been reported, and in such cases most patients require a second procedure. 2,5,[9][10][11][12] These complications lead to delayed post-operative chemotherapy and a poor oncological and functional outcome. 1,2,11,13 Possible reasons for the significantly high rate of complications after pelvic surgery include insufficient soft-tissue cover and a large dead space after wide excision.…”
mentioning
confidence: 99%
“…In one large case series, Senchenkov et al [18] reported flap necrosis of 13% (eight of 60 cases) for posterior flap closure and 37.5% (three of eight cases) for anterior flap closures. Wound infection, however, is reported to range from 17% to 46%, depending on the level of ligation of the iliac vessels [19]. We attribute good wound healing in our patients to the large muscle mass of the adductor compartment and its fairly abundant blood supply.…”
Section: Discussionmentioning
confidence: 72%
“…Early operative management, consisting of nerve grafts and nerve transfers, has been accepted as the standard of care for total plexus injuries [11]. However there is no consensus regarding the indications for and timing of surgical management for subtotal obstetrical brachial plexus injuries.…”
Section: Discussionmentioning
confidence: 99%
“…If the child fails the Cookie Test operative management is recommended. In cases selected based on the surgeons' experience surgery may be recommended at 6 months of age if there has been little or no improvement since the 3-month visit and the probability of passing the Cookie Test if recovery was allowed until 9 months of age is deemed to be small [11]. …”
Section: Introductionmentioning
confidence: 99%